Evaluation of long-term outcomes following acute coronary syndrome in the clinical practice: results of the 5-year follow-up - I. S Skopets; N. N Vezikova; O. Yu Barysheva; A. V Malafeev; A. N Malygin; A. V Leontyev; A. A Ispravnikova (КардиоСоматика, 2018)
The article presents the results of the 5-years follow-up for the patients who had acute coronary syndrome. The results of the hospital treatment were demonstrated. In addition, the study showed the adherence to the therapy, long-term consequences and clinical outcomes following acute coronary syndrome in the clinical practice in the Republic of Karelia